Evaluation of the enantioselective in vitro metabolism of the chiral pesticide fipronil employing a human model: Risk assessment through in vitro-in vivo correlation and prediction of toxicokinetic parameters. (January 2019) - Carrão, Daniel Blascke; dos Reis Gomes, Isabel Cristina; Barbosa Junior, Fernando; de Oliveira, Anderson Rodrigo Moraes
Abstract: The chiral pesticide fipronil is employed as a racemic mixture to control pests. Although there are no enantioselective differences in the fipronil enantiomer activities toward target organisms, fipronil enantiomers may exhibit enantioselective differences in their bioaccumulation, toxicity, and metabolism toward non-target organisms, including humans. The present work aims to provide significant reliable enantioselective information concerning fipronil risk assessment in humans. For that, the in vitro metabolism of rac -fipronil, S-fipronil, and R-fipronil by human liver microsomes was evaluated, the in vivo enantioselective toxicokinetic parameters were predicted and the main CYP450 isoforms involved in the enantioselective metabolism were determined. The obtained results demonstrated that fipronil may undergo a clearance by the liver and it is exclusively metabolized by the CYP3A4 isoform. Although no significative stereoselective differences were observed, the results provide reliable information on fipronil risk assessment for humans. Graphical abstract: Highlights: The enantioselective kinetic parameters for fipronil metabolism were determined. The in vivo toxicokinetic parameters were predicted from the in vitro data. Fipronil is metabolized by the liver. CYP3A4 is the only isoform involved in fipronil human metabolism. No significative enantioselective difference was observed in fipronil metabolism.